Ultrahigh sensitive carbon-based conducting rubbers for flexible and wearable human-machine intelligence sensing - Ajeev, Arya; Javaregowda, Bharathkumar H.; Ali, Ashik; Modak, Mrudul; Patil, Shreya; Khatua, Saumyakanta; Ramadoss, Marimuthu; Kothavade, Premkumar Anil; Arulraj, Arul Kashmir (Advanced Materials Technologies, 2020)
The wearable strain sensors with multifunctional applications can fuel the rapid development of human-machine intelligence for various sectors like healthcare, soft robotics, and Internet of Things applications. However, achieving the low-cost and mass production of wearable sensors with ultra-high performance remains challenging. Herein, a simple, cost-effective, and scalable methodology to fabricate the flexible and highly sensitive strain sensors using carbon black and latex rubbers (LR) is presented. The LR-based strain sensor demonstrates excellent flexibility, fast response (approximate to 600 ms), ultra-high sensitivity (maximum gauge factor of 1.2 x 10(4) at 250% strain), and long-term stability over 1000 cycles. The LR-based strain sensors are sensitive to monitor subtle human motions such as heart pulse rate and voice recognition along with high-strain human joint operations. Additionally, the sensing mechanism of LR bands is investigated by surface topographies and electromechanical response under various strained/unstrained conditions. Further, a smart glove-based sensor module made of LR strain bands with an Arduino reader for the human-machine intelligence device for non-verbal communication in military applications is demonstrated.
Keywords: conducting rubbers; gauge factor; human– machine interfacing; voice recognition; wearable strain sensors

Unsymmetrical squaraine dyes for dye-sensitized solar cells: position of the anchoring group controls the orientation and self-assembly of sensitizers on the TiO2 surface and modulates its flat band potential - Singh, Ambarish Kumar; Maibam, Ashakiran; Javaregowda, Bharathkumar H.; Bisht, Rajesh; Kudlu, Ashwath; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of Physical Chemistry C, 2020)
The position of the anchoring group is systematically changed with a series of alkyl group wrapped donor-acceptor-donor (D-A-D) based squaraine dyes, 4-SQ to 7-SQ, for the use in dye-sensitized solar cells (DSSCs). By this approach, the orientation as well as the self-assembly of the sensitizers can be controlled on the semiconducting TiO2 surface. All of the dyes functionalized with hydrophobic alkyl groups at sp(3)-C and N atoms of the indoline units that is far away from the TiO2 surface to control the self-assembly of dyes and passivate the surface. Controlling both the orientation as well as the self-assembly of the sensitizers synergistically enhances the V-oc of the DSSC device by imparting the dipole moment on the TiO2 surface and minimizing the interfacial charge recombination process of electrons from TiO2 to the oxidized electrolyte, respectively. Further, the presence of a meta-carboxyl group with respect to the N atom of the indoline donor unit for the dyes 4-SQ and 6-SQ makes them nonconductive for the charge injection process, which sheds light on the importance of through-space electron transfer for the device performance. Emission from the relaxed twisted state was found to be a deactivation pathway for 4-SQ on TiO2 and ZrO2, which revealed the importance of structural factors that promote spatial interaction between the sensitizer and metal oxide surface. Computational studies showed the systematic changes in the dipole moment for the sensitizers 4-SQ, 5-SQ, and 6-SQ upon anchoring to the TiO2 surface. The DSSC device performance varied with the position of anchoring groups in the sensitizers. The DSSC device performance of 5-SQ indicates a J(sc) value of 11.35 mA cm(-2), V-oc of 0.698 V, and ff of 77% corresponding to a power conversion efficiency of 6.08% in the presence of 3 equiv of coadsorbent CDCA, which is nearly 1.5 times higher than 6-SQ (V-oc 0.7 V, J(sc) 7.76 mA cm(-2), ff 76%, and eta 4.14%) and 2.6 times higher than 4-SQ (V-oc 0.658 V, J(sc) 4.42 mA cm(-2), ff 78%, and eta 2.28%). IPCE studies revealed the importance of orientation for the charge injection and self-assembly of dyes, as devices with 5-SQ and 6-SQ as a sensitizer showed 94 and 77% response at 578 nm, respectively, which correspond to the aggregated structure of the dye. Mott-Schottky and IPCE experiments showed that the orientation of sensitizers could modulate the V-oc due to the shift in the flat band potential of TiO2.

Partially bio-based triarylamine-containing polyimides: synthesis, characterization and evaluation in non-volatile memory device applications - Chatterjee, Deepshikha; Jadhav, Uday A.; Javaregowda, Bharathkumar H.; Dongale, Tukaram D.; Patil, Pramod S.; Wadgaonkar, Prakash P. (European Polymer Journal, 2021)
A new triarylamine-containing diamine, viz. 4, 4'-diamino-4 `' pentadecyltriphenylamine was synthesised starting from cashew nut shell liquid (CNSL) - a non-edible by-product of cashew processing industry. Three new partially bio-based triarylamine-containing polyimides were synthesised by one-step high temperature solution poly-condensation of 4, 4'-diamino-4 `' pentadecyltriphenylamine with aromatic dianhydrides, namely, 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 4,4'-oxydiphthalic anhydride (ODPA) and 4,4'-(hexa-fluoroisopropylidene) diphthalic anhydride (6-FDA). Polyimides were determined to be of reasonably high molecular weights as inherent viscosity and number average molecular weights (M-n, Polystyrene standard) values were in the range 0.54-0.60 dL g(-1) and 26,800-43,500 g mol(-1), respectively. Polyimides exhibited excellent solubility in common organic solvents and film-forming nature along with reasonably good thermal properties as indicated by temperature for 10% weight loss (T-10) and glass transition temperatures (T-g) which were in the range 418-447 and 165-225 degrees C, respectively. The optical and electrochemical band-gap values were in the range of 1.95-1.98 eV and 1.671-1.745 eV, respectively. Among triarylamine-containing polyimide devices, BPDA-based device showed acceptable current-voltage and non-volatile memory properties such as the endurance of 500 cycles and 1000 s of retention time. The conduction mechanism developed in the memory devices was also explored and was found to follow Ohmic and Schottky conduction mechanisms.
Keywords: Bio-based polyimides; CNSL; Memory device; pentadecyl; Triarylamine

Modular TiO2-squaraine dyes/electrolyte interface for dye-sensitized solar cells with cobalt electrolyte - Singh, Ambarish Kumar; Sudhakar, Vediappan; Javaregowda, Bharathkumar H.; Bisht, Rajesh; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Chemphotochem, 2023)
Strategies to diminish both charge recombination and aggregation of dyes on the photoanode by functionalizing the sensitizer with alkyl groups is the best approach to achieve high dyesensitized solar cell (DSSC) efficiency. Development of such a photoanode with NIR-active dyes which is compatible with a cobalt electrolyte is important to enhance the photovoltaic performance. In this report, alkyl-group-wrapped donor-acceptor-donor (D-A-D) based unsymmetrical squaraine dyes have been used for DSSC device characterization with a cobalt electrolyte. Surface passivation of photoanode was varied systematically by the extent of functionalization with alkyl groups to avoid charge recombination. DSSC device performance of 5.92% was achieved for an alkyl-group-wrapped squaraine dye with a cobalt electrolyte. Hence, appending the alkyl groups on the donor unit of squaraine dyes helps passivating the photoanode, whereas introducing hydrophilic groups provides a leaky surface where oxidized electrolyte species reach the titanium-metal-oxide surface which promotes the charge recombination process.
Keywords: counter-electrode; DSSC device efficiency; Dye-sensitized solar cells; Electrolytes; unsymmetrical squaraine dye

Organic field effect transistors comprising copolymers synthesized without structure-directing moieties with enhanced carrier mobility - Swain, Gitanjali; Javaregowda, Bharathkumar H.; Dambhare, Neha V.; Krishnamoorthy, Kothandam (ACS Applied Electronic Materials, 2023)
Conjugated materials are synthesized by C-C bond formation reactions. Trimethyltin and boronic acid are two widely used structure-directing moieties. While using the ethynyl moiety as a part of the monomer, additional structure-directing moieties are not needed. However, ethynylene will be part of the conjugated material. Often, the polymers with an ethynylene moiety negatively impact the polymers' properties. However, the ethynylene moiety could minimize the dihedral angle if the monomer has steric functionalities. For example, BODIPY is an attractive monomer due to its high molar extinction coefficient, partial quinoidal character, and high quantum yield. However, materials based on BODIPY exhibited poor charge carrier mobility due to steric hindrance generated by four methyl groups. Herein, we copolymerize BODIPY with ethynylene comprising i-indigo and thieno-i-indigo. The copolymer with thieno-i-indigo showed increased molecular weight and significantly reduced band gap compared to the copolymer with i-indigo. The copolymer with i-indigo showed immeasurably low hole transport mobility. On the other hand, the copolymer with thieno-i-indigo exhibited 0.003 cm2V(-1) s(-1). These measurements were made using field effect transistors. We also measured the charge carrier mobility using the space charge-limited current method. Both copolymers exhibited a mobility of 10(-3) cm(2) V-1 s(-1).
Keywords: acetylene linkage; BODIPY; field effect transistor; iso-indigo; Sonogashira coupling; thienoisoindigo

MOFite: a high-density lithiophilic and scalable metal-organic framework anode for rechargeable lithium-ion battery - Gaber, Safa; Mohammed, Abdul Khayum; Javaregowda, Bharathkumar H.; Martinez, Jose Ignacio; Sanchez, Pilar Pena; Gandara, Felipe; Krishnamoorthy, Kothandam; Shetty, Dinesh (ANGEWANDTE CHEMIE-INTERNATIONAL EDITION, 2024)
Keywords: conjugated MOF; Energy storage; lithium ion battery; Metal-organic framework; scalable synthesis

Shuttle balance between lithiophilic functionalities substituted on conjugated polymers to improve lithium-ion diffusion and cycling stability of batteries - Kargude, Radhakisan; Javaregowda, Bharathkumar H.; Palani, Sathishkumar; Singh, Anup K.; Krishnamoorthy, Kothandam (Macromolecules, 2024)
Herein, we report the design and synthesis of i-Indigo and trans-1,2-di(2-thienyl)ethylene (TVT) comprising copolymers with various side chains that are used as anode-cum-binder in Li-ion batteries. The TVT disrupts the crystallinity, and the i-Indigo renders the handle for unsymmetrical substitution. Polymer P1 comprises alkyl chains on i-Indigo, whereas P2 comprises an alkyl chain and a chain with a urethane moiety as another side chain. Polymer P3 comprises i-Indigo with a urethane moiety and triethylene glycol as side chains. The i-Indigo in P4 is substituted with triethylene glycol and alkyl chains as side chains. These polymers were found to be amorphous with pi-pi stacking due to the extremely small torsional angle imparted by TVT moieties. All of these polymers showed comparable specific capacity while used as an anode in Li-ion batteries due to the presence of a common conjugated backbone. However, the battery metrics varied significantly while the current density of the batteries varied between 0.1 and 2.0 A g(-1). P1 and P2 showed a very close recovery of specific capacity at 0.1 A g(-1) before and after various current densities. However, polymers P3 and P4 did not recover from the specific capacity fading due to the presence of triethylene glycol side chain that degraded. Polymer P2 with an alkyl side chain and a chain with a urethane moiety showed stable performance over 2000 charge-discharge cycles. Contrary to this, the stability of polymers with triethylene glycol side chains decreased over 2000 charge-discharge cycles. Polymer P2 with a urethane side chain also showed improved Li-ion diffusion because the urethane moiety facilitated better Li-ion transport.

Synergistic effect of lactam and pyridine nitrogen on polysulfide chemisorption and electrocatalysis in lithium sulfur batteries - Javaregowda, Bharathkumar H.; Kargude, Radhakisan; Birajdar, Sarika; Shivankar, Bhavana; Krishnamurty, Sailaja; Jones, Lathe A.; Caruso, Rachel A.; Krishnamoorthy, Kothandam (ACS APPLIED MATERIALS & INTERFACES, 2024)
Keywords: Li-S battery; phenyl-diketopyrrolopyrrole; pyridine-diketopyrrolopyrrole

Diamondoid all-carbon porous aromatic framework host for lithium-sulfur batteries - Kumar, Viksit; Javaregowda, Bharathkumar H.; Devasia, George; Narayanan, Aswini; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Babu, Sukumaran Santhosh (Small, 2025)
Lithium-sulfur batteries (LSBs) hold incredible potential as next-generation energy storage systems. However, practical applications of LSBs are significantly hindered by several critical challenges. For the first time, scalable all-carbon porous 3D polymers (3DPs) that do not contain heteroatoms or functional groups and do not require post-functionalization are investigated as hosts in lithium-sulfur batteries, demonstrating enhanced cycling stability and overall battery performance. The pyrene-containing 3DP exhibits 75% capacity retention after 600 cycles at 1 C and 52% capacity retention after 1300 cycles at 0.2 C, better than phenyl comprising 3DP. Furthermore, even at higher sulfur loading (4.1 mg cm(-2)) with an electrolyte/sulfur ratio of 5 mu L mg(-1), pyrene 3DP displayed a high capacity of 600 mA h g(-1) and stable performance over 250 cycles with negligible capacity fade. The defined pore structure of 3DPs prevents the migration of polysulfides through physical confinement and the large pi -clouds of 3DPs interact with the negative charge-bearing polysulfides generated in charge-discharge cycles through anion-pi interaction. In this way, The design ensures that the host 3DPs interact with neutral sulfur and anionic polysulfides, resulting in an excellent performance.
Keywords: 3D polymers; Batteries; Li-Sulfur battery; porous materials; pyrene

Heteroatom-synergistic effect on anchoring polysulfides in chalcone-linked nanographene covalent organic frameworks for high-performance Li―S batteries - Ranjeesh, Kayaramkodath Chandran; Javaregowda, Bharathkumar H.; Gaber, Safa; Bhauriyal, Preeti; Kumar, Sushil; Skorjanc, Tina; Finsgar, Matjaz; Heine, Thomas; Krishnamoorthy, Kothandam; Shetty, Dinesh (Advanced Science, 2025)
Lithium-sulfur (Li & horbar;S) batteries are an attractive option for future energy storage devices because they offer higher theoretical specific capacity, energy density, and cost-effectiveness than commercial lithium-ion batteries. However, the practical applications of Li & horbar;S batteries are significantly limited by the shuttle effect caused by intermediate lithium polysulfides (LiPSs) and slow redox kinetics. In this study, the molecular engineering of chalcone-linked, sp(2)-bonded nanographene-type covalent organic frameworks (COFs) as sulfur hosts is reported to enhance interactions with LiPSs, thereby effectively suppressing the shuttle effect. The developed sulfur-hosting cathode material demonstrated outstanding battery performance, surpassing most reported materials by achieving a specific capacity of 1228 mA h g(-1) at 0.5C, with 80% retention after 500 cycles and an average Coulombic Efficiency (C.E.) of 99%. Additionally, the mechanisms of sulfur immobilization, the subsequent conversion into lithium polysulfides (LiPSs), and their binding energies with COFs are investigated using density functional theory (DFT) calculations. These findings offer valuable insights into the structure-property relationships essential for developing more efficient sulfur-hosting cathodes.
Keywords: anion-pi interaction; covalent organic frameworks; lithium-sulfur battery; nanographene; polysulfide shuttle

Mechanochemical large-scale rapid synthesis of ultrapure sodium hexafluorophosphate - Senthilkumaran, Marimuthu; Javaregowda, Bharathkumar H.; Rajendran, Prakash Babu; Balasubramanian, Rajalakshmi; Ajithkumar, Thalasseril G.; Ravindranathan, Sapna; Krishnamoorthy, Kothandam (ChemPlusChem, 2025)
Among the sodium battery electrolytes, sodium hexafluorophosphate (NaPF6) exhibits superior conductivity, anodic stability, and stable cathode electrolyte interface compared to other electrolytes. Therefore, the synthesis of pure NaPF6 through a simple process is very important. Usually, NaPF6 is synthesized using HF. In our approach, NaPF6 is synthesized by grinding dry ammonium hexafluorophosphate (NH4PF6) and sodium metal. Sodium injects an electron into the ammonium ion, which results in the formation of ammonia and hydrogen. The gram scale synthesis is completed in about 30 min. Purification of the product is not needed. The product purity is confirmed by various spectroscopic and electrochemical techniques. Usually, NaPF6 comprises NaF, HF, and solvents as impurities that affect the performance of SIBs. It has been confirmed that the NaPF6 synthesized by our mechanochemical approach in the absence of solvent is devoid of impurities despite the absence of product purification step. Furthermore, the synthesis of pure NaPF6 (250 g) is demonstrated using a grinder used as household item in cooking Indian pancakes, which costs about 300 USD. The duration of the synthesis of 250 g pure NaPF6 is 1 h. The purity of this sample is comparable to that of NaPF6 (5 g) synthesized using mortar and pestle.
Keywords: ammonium hexafluorophosphate; Batteries; carbonates; sodium hexafluorophosphate; sodium vanadium phosphate

Utilizing nature's endowment: artificial leaf concept for methane activation to C-C coupled ethanol or ethylene - Kanungo, Subhashree S.; Mishra, Abhaya Kumar; Avani, Mangaladasan J.; Bajpai, Himanshu; Salgaonkar, Kranti N.; Javaregowda, Bharathkumar H.; Gopinath, Chinnakonda S. (Sustainable Energy & Fuels, 2025)
Methane activation (MA) to platform chemicals under ambient conditions still remains an open challenge to be fully realised. The present work shows the fabrication of CeVO4 quantum dots (CV-QDs) by a bottom-up approach; they are assembled from Ce3+ and metavanadate ions, and structurally and electronically integrated into the micro-/meso-pores of TiO2 (CV-QD-TiO2 (CVT)), demonstrating the conversion of MA to ethanol/ethylene by visible light-driven photocatalysis. CV-QDs in confined pores modify the quantum confinement effects and are characterized by physicochemical methods. The current synthetic strategy is potentially scalable and results in sub-quadrillion heterojunctions in a 1 mg CVT photoanode spread over 1 cm2. MA with CVT under one-sun conditions demonstrates similar to 100% selectivity to ethanol, yielding 4.36 mu mol h-1 cm-2, with a solar-to-fuel efficiency (STFE) of 0.56. Further, by employing a co-catalyst, significant STFE (5.08) and yield (39.5 mu mol h-1 cm-2) are achieved selectively towards ethylene. A deliberate addition of methanol increases the rate of ethanol production by 17.2 times, indicating that the methyl-methoxy interaction is the origin of C-C coupling. Weight is normalized to a gram of CV-QDs in a large area CVT photoanode to yield 109 mmol h-1 gCV-QD-1 of ethanol and 988 mmol h-1 gCV-QD-1 of ethylene. Enhanced activity and selectivity towards the C2-product is attributed to band-edge modulation and trillions of heterojunctions, which in turn facilitate charge separation and charge transfer for effective charge utilisation at redox sites.

Orthogonally Engineered Redox-Active Polyimide-Carbon Nanotube Hybrids for Long-Life Lithium-Ion Battery Cathode - Thanasekar, Chandragopal; Javaregowda, Bharathkumar H.; Veer, Sairam Dnyaneshwar; Devasia, George; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Babu, Sukumaran Santhosh (Small, 2026)
The diverse structural tunability and engineered electronic properties of organic polymers have sparked significant interest in their use as cathode materials for lithium-ion storage. Recent advances suggest that organic cathodes can serve as promising alternatives to conventional metal oxide counterparts due to their elemental abundance, safety, and high theoretical capacity. However, developing cathode materials that simultaneously exhibit high specific capacity, long cycle life, and excellent rate performance remains a critical challenge. In this study, the synthesis and application of a redox-active polyimide based on orthogonally positioned, active site-rich mellitic trianhydride (MTA) and naphthalene diimide (NDI), integrated with multi-walled carbon nanotubes (MWCNTs), referred to as MTA-NDI@CNT are reported. The pristine MTA-NDI polymer demonstrates a specific capacity of 60 mAh g-1 at a current density of 200 mA g-1 and exhibits remarkable cycling stability over 20 000 cycles. Upon hybridisation with CNT (10 wt.%), the composite (MTA-NDI@CNT) delivers a nearly threefold enhancement in specific capacity, reaching 170 mAh g-1 at 500 mA g-1, along with stable cycling performance over 1300 cycles and 60.5% capacity retention.
Keywords: cathode; CNT; lithium-ion battery; orthogonality; Polyimide